2016
DOI: 10.1080/02656736.2016.1194485
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and its predictor in microwave ablation for severe secondary hyperparathyroidism in patients undergoing haemodialysis

Abstract: Baseline iPTH level is a good predictor of MWA efficacy for severe secondary hyperparathyroidism; parathyroidectomy is more effective for severe secondary hyperparathyroidism than MWA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 32 publications
1
21
2
Order By: Relevance
“…Compared to other kinds of thermal ablation, such as radiofrequency ablation and laser ablation, MWA has several advantages including a more predictable ablation zone, ability to simultaneously treat multiple lesions, large ablation volumes, and fast ablation times . To compare the efficacy of MWA and parathyroidectomy for SHPT, Diao et al conducted a study in 30 patients undergoing maintenance hemodialysis and concluded that parathyroidectomy was more effective for severe SHPT than MWA . However, our study, with a larger sample size of 81 cases, showed that MWA was more effective for severe SHPT than parathyroidectomy.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Compared to other kinds of thermal ablation, such as radiofrequency ablation and laser ablation, MWA has several advantages including a more predictable ablation zone, ability to simultaneously treat multiple lesions, large ablation volumes, and fast ablation times . To compare the efficacy of MWA and parathyroidectomy for SHPT, Diao et al conducted a study in 30 patients undergoing maintenance hemodialysis and concluded that parathyroidectomy was more effective for severe SHPT than MWA . However, our study, with a larger sample size of 81 cases, showed that MWA was more effective for severe SHPT than parathyroidectomy.…”
Section: Discussioncontrasting
confidence: 59%
“…Diao et al also demonstrated that baseline iPTH level was an independent predictor of MWA efficacy for severe SHPT, and a threshold value of 1493.7 pg/ml yielded higher sensitivity and specificity . However, the OR value of 0.997 (95% CI, 0.994–0.999) in that study was very close to the critical point.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The studies covered a period !8 years, from 2009 to 2017. Two were retrospective cohort studies [26,27], and six were retrospective self-control studies [28][29][30][31][32][33]. The mean follow-up period ranged from six to 23 months, and the sample size ranged from 9-56 patients.…”
Section: Discussionmentioning
confidence: 99%
“…The phosphorus measurements obtained one day after MWA were significantly lower than those obtained before MWA (WMD: 0.289, 95% CI: 0.163-0.415, p < 0.01) (Figure 4(A)). Four articles reported phosphorus measurements obtained at one week [26,27,29,30] and one month [26,27,29,31], respectively, after MWA. The heterogeneity among studies was significant, so the random-effects model was used for the analysis (p < 0.01, I 2 ¼ 86.5%; p < 0.01, I 2 ¼ 85.3%).…”
Section: The Change Of Phosphorusmentioning
confidence: 99%